La comunicación interna y su incidencia en el clima laboral de la empresa Maribella-Latacunga. - Caguano Timbila, Jessica Paola (2023)
The research aims to identify the impact of internal communication on the work environment of the company, Dairy Products Maribella-Latacunga city, from the perspective of its employees, considering the crucial role that these factors play in the business environment. A positive work environment characterized by satisfaction, motivation and collaboration is fundamental for the company's performance and productivity. For this reason, the research has a quantitative approach, with a descriptive level. For the lifting of information, a survey is applied, through the internal communication and work climate instrument of the author Maria Graciela Barrantes Rivera (2018), in combination with the Likert scale under the following dimensions: Communication Strategies, Communication Tools, Internal Audience, Job Performance, Job Satisfaction and Job Motivation, the results obtained from the company's employees show that the internal work environment has the highest rating of Always and Almost Always. The company has activities that allow the development of work activities in an adequate work environment, as well as, perceive that the company provides them with facilities for personal, professional and emotional progress, generating positive teamwork. The investigation proposes the development of a strategic plan to strengthen the organization's internal communication and work environment, the benefits to be gained from the strategic strengthening plan are: improved relations between managers and peers to have an assertive communication, to contribute to the formation of business leaders, to stimulate positive activities, to strengthen the personal, professional and institutional life project, which is reflected in a good working environment.